Intelligent Buildings as Cyber-Physical Systems: a Reconfigurable Hardware Technology-based Approach - Szász, Csaba (Recent Innovations in Mechatronics, 2020)
This paper discusses the idea to change the way to approach intelligent buildings (IBs) development and implementation by taking into account the last evolutions in cyber-physical systems (CPSs). Therefore, the main goal is to extend IBs design engineering with the constraints of systems in a CPS context. As well known, smart buildings are increasingly complex as they integrate many scientific areas and research topics, as well as a large scale of last-generation technologies. At the same time, the Internet has deeply transformed the way to manage information and services, respectively how information is transmitted and computed in cyberspace. The quick management and information processing inside cyber layer challenges the interaction with the physical world in a sense to develop IBs as smart distributed systems or CPSs. In addition to this, the papers emphasize the original idea of developing reconfigurable hardware technology-based (RHT-based) CPS architectures for IBs implementation purposes. The benefits of the RHT application in a CPS context for IBs are widely discussed and analyzed. The unfolded theoretical background has been supported by an implementation example using last generation software technologies. These experiments evidence the advantages and versatility of this challenging implementation paradigm of the latest digital technology, applied for current-state IBs development.